Principles of intellectual property - Gopalakrishnan, N. S. Dr.; Agitha, T. G. (Lucknow : Eastern Book Co., 2009)
In Indian context.
Includes bibliographical references.
Keywords: Intellectual property -- India; Intellectual property -- India -- Cases